Ethics in educational technology: a perspective in the light of philosophical texts on technique. (2020)
This chapter refers to hermeneutical research. Its purpose is to reflect on the need for an ethics of technology in its educational use, based on the texts of three contemporary 20th-century philosophers who were interested in the subject of technique: Ortega & Gasset, Heidegger, and Mayz Vallenilla. This review leads to propose seven postulates that are proposed to ethically guide the growing use of technology in the various educational spaces. The postulates are 1. We are humans, not gods; 2. Being prevails above possessing and being useful; 3. Promoting a culture of austerity, not of consumption or discard; 4. The technique is at the service of living; 5. There are fruitful relationships between art, poetry, and technique; 6. Increasingly humane and comprehensive education is urgent; 7. The technique must lead the way to transcendence.